Implementasi Gerakan Literasi Sekolah di SMP Muhammadiyah 01 Jember - Fatqurhohman, Fatqurhohman; Fatkurochman, Henri; Prastzuba, Falestin Al-Zakiyah; Diniyah, Putri Holifatur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The role of human resources for teachers (educators) in technological progress in the era of the Industrial Revolution 5.0 makes the world of education the most important part of changing the nation's civilization, because it is the implementer of the success of the learning process in the classroom. The government's policy on independent learning hopes to have a positive impact through various activities to grow and improve a culture of literacy, competence and character. Therefore, this service provides a form of service through the socialization of the school literacy movement in independent curriculum learning at SMP Muhammadiyah 01 Jember. The results of this service have provided an understanding of the importance of carrying out a massive school literacy movement by providing access to reading and providing facilities to students. This activity has strengthened the importance of teacher competence in developing and implementing ideas for literacy culture in schools through a text-rich environment, an affective social environment, an appropriate academic environment according to the independent curriculum, and providing a creative environment (makerspace). Thus, this service activity can have a positive impact on schools, especially teachers as implementers of the success of the learning process in the classroom in increasing student competence